Pregled organiziranosti knjižničnih storitev za slepe in slabovidne v izbranih državah - Vovk, Damjana (Knjižnica, 2011)
Purpose: Models of organization of library services for the blind and partially sighted from the view of special and public librarianship in selected countries were examined. In addition, theoretical and legislative frameworks, professional guidelines and trends are explored. Some terminological inconsistencies and obstacles in performing the services are also presented. Methodology/approach: The explorative-comparative study carried in the years 2008-2010 includes the comparative analysis of data acquired by the survey and literature desktop research. The research sample included 14 countries - eleven European countries, USA, Australia, and Canada. Results: The findings show great varieties among the selected countries, however, there is the trend of moving the organization of services based on a private charitable association to the formalized state supported system. The majority of countries have applied the centralized model with one specialized (national) library. There is rarely a case of formal inclusion of public libraries in the organization of services. Recent major professional interests in the field of providing library services to visually impaired are broadening the copyright exceptions and user groups, and the implementation of information technology for bigger production of alternative formats and availability of library materials. Research limitation: The low rate of survey response and the differences in the organization of library services influenced on the lack of data and low level of data comparability. Originality/practical implications: The results are useful for designing a model of library services in Slovenia.
Keywords: javne knjižnice; uporabniki s posebnimi potrebami; slepi; slabovidni; knjižnične storitve; primerjalna analiza